Exploring the Characteristics of Islamic Architecture in Educational Buildings: A Study of a Few Selected Muslim Countries - Almaimani, Ayad (Journal of King Abdulaziz University: Environmental Design Sciences, 2023)
Sustainability is one of the words that can be utilized in various approaches and meanings. This research discusses the sustaining of architectural design styles that are related to Islamic civilization and heritage. Institutional buildings (i.e., educational buildings) those are involved in teaching Islamic education are somewhat following a few special sets of design criteria for their unique architectural design sustainance that lead to permanence to be located in mostly the urban areas. The Islamic Madrasa buildings (i.e., Sunni in particular) from the perspective of architectural design, materials, constructional methods, structural methods, and other approaches adopted solutions express the sustainable capabilities of the Islamic architectural Building types. This research paper intends to highlight the need for a tool for assessing institutional buildings and assembling critical information to understand similarities of architectural design based on several evaluation criteria mostly in an urban setting. In doing so, the researcher has conducted a qualitative research approach for collecting primary and secondary information from several institutional buildings around the world. Furthermore, the researcher has evaluated building plans, designs, and interior facilities of institutional buildings by collecting information from reliable websites. Note that the researcher has explored the existence of building facades, courtyards, staircases, building materials, color, water supply arrangements, and floor designs of the studied educational buildings in common. After summarizing the information, the researcher insinuates that the evaluation method adopted in this study may be useful for understanding and assuring the continuity of Islamic architecture styles of educational buildings (Madrasa) in Islamic countries.